Methods and variations of creating organizational and technological model of renovation objects - Lapidus, Azariy Abramovich; Topchiy, Dmitriy Vladimirovich (Revista de la Universidad del Zulia, 2019)
This article presents a study of links in organizational and technological structures and information support in construction control in the Russian Federation and other countries, including Great Britain, the USA, Germany, etc. It describes particular features of interconnection between the customer and the general contractor in construction product quality management abroad and substantiates the need for development of an automated design system of construction quality management. The study presents the structure of the state construction supervision in Russia at the objects of industrial and civil purposes. It reveals the features of conducting supervisory activities in construction and presents the main aspects of such activities. The article describes in detail the differences between the implementation of supervision and construction control on capital construction projects. The article gives an example of methods and variations of creating organizational and technological model of renovation objects. Creating an organizational system for the completion of construction of non-preserved and unfinished facilities is based on identifying and creating basic coefficients affecting the production organization efficiency. It also forms the basis of a single organizational and managerial model which enables a project to be implemented in the very short term and at minimal cost.